Sensory loss due to object formation. (September 2020) - Mamassian, Pascal; Zannoli, Marina
Abstract: The precision to locate individual features in depth can often be improved by integrating information over space. However, this integration can sometimes be extremely detrimental, as for example in the case of the Westheimer-McKee phenomenon where features are grouped to form an object. We replicate here the known loss of precision in this phenomenon and document an additional loss of accuracy. These detrimental effects are still present when the object is elicited by other principles of organization, including a cross-modal auditory cue. Similar effects of object formation are found on lateral motion sensitivity. We then present a simple probabilistic model based on the integration of estimated depth within an object and propagation of object mean depth and uncertainty back to the elementary features of the object. This propagation of object uncertainty is a hitherto underestimated side-effect of object formation.